The use of Ptolemaic terracotas for research into domestic religions and personal piety of egyptian warriors. Selected examples - Jędraszek, Sławomir (Acta Archaeologica Lodziensia, 2021)
The subject of the following article is the problems surrounding the interpretation of Egyptian military terracotta figurines representing Egyptian deities from Hellenistic period. In the present paper, I will attempt to find an answer to the question the study of this class of objects permits us to answer contemporary questions concerning the personal (individual) piety, worship, household cult and religion. Special attention will be given to the Egyptian elite: especially soldier/priests – officers with priestly functions, which from the second century BC the Ptolemaic rulers recruited from among Egyptians families, and to the native military class, whom the Greeks called machimoi. The iconographic range of this category of objects is very wide, and I also intend to raise certain aspects of the iconographic analysis. I will concentrate above all on Egyptian deities such as the protective, dwarf god Bes, especially in his military forms. Then I shall turn to the god Harpocrates, the son of Osiris and Isis, a manifestation of Horus, showing his military manifestations (often fully armed). These terracotta figurines might conceivably function in the domestic practice of several types of ritual. The worship of deities where the terracotta served as a cult image of deities, also in the royal cult, and in the performance of magical rites. This article is, therefore, not only concerned with the iconographic analysis of chosen terracotta examples of a single deity, such as Bes or Harpocrates, but also presents social background of the lower-level soldiers, and officers with priestly functions within the Ptolemaic army.